Dosis Y Épocas De Aplicación De Nicosulfuron En El Cultivo De Maíz En La Localidad De Babahoyo, Ecuador - Luis Alcívar-Torres; Dalton Cadena-Piedrahita; Juan Salinas-Ochoa; Miguel Goyes-Cabezas; Danilo Santana-Aragone (European Scientific Journal, ESJ, 2016)
This study evaluated the effect of three doses of nicosulfuron postemergent herbicide(40, 50 y 60 gr/ha), applied in three moments of the vegetative stage of hybrid corn “Trueno NB – 7443” (12, 18 and 24 days after sow), using two levels of fertilization (76 – 15 – 90 and 152 – 30 – 180 of N - P2O5 y K2O Kg., respectively) and one population (71.428 plants/ha). The experiment is performed on a total area of 1857.6 m2 and each experimental unit had an area of 16.8 m2; the experimental design was randomized complete block factorial arrangement of 2 x 9 with a total of 18 treatments and 4 repetitions. The toxicity index and other agronomic indicators of production depending on the dose and time of application of herbicide are determined. The results showed phytotoxicity on selectivity only 3 days evaluation after herbicide application in different doses. Treatment based on 40 g / ha of herbicide applied at 12 dds, in the presence of 76 levels and 152 -15- 90 -30 -180 kg / ha NPK, he had the lowest toxicity index and concluded that the levels of fertilization did not influence the susceptibility of the hybrid corn used.